Promising inhibition of diabetes-related enzymes and antioxidant properties of Ptilostemon casabonae leaves extract - Cinzia Sanna; Antonella Fais; Benedetta Era; Giovanna L. Delogu; Enrico Sanna; Laura Dazzi; Antonella Rosa; Arianna Marengo; Patrizia Rubiolo; Antonio De Agostini; Sonia Floris; Francesca Pintus (Taylor & Francis Group, 2023)
Type 2 diabetes (T2D) is a progressive metabolic disorder of glucose metabolism. One of the therapeutic approaches for the treatment of T2D is reducing postprandial hyperglycaemia through inhibition of the digestive enzymes α-glucosidase and α-amylase. In this context, aimed at identifying natural products endowed with anti-T2D potential, we focused on Ptilostemon casabonae (L.) Greuter, a species belonging to Asteraceae family. Enzymatic inhibition, antioxidant activity, phenolic composition and cellular assays were performed. This study revealed that the P. casabonae hydroalcoholic extract exerts a potent inhibitory activity against α-glucosidase. This activity is supported by an antioxidant effect, preventing ROS formation in a stressed cellular system. HPLC-PDA-MS/MS analysis, revealed a complex polyphenolic fraction. Among the tested pure compounds, 1,5-dicaffeoylquinic acid, apigenin and rutin displayed good α-glucosidase inhibitory activity. Our study suggested new potential of P. casabonae encouraging us to further testing the possible therapeutic potential of this extract.